2015
DOI: 10.1007/s11605-014-2688-9
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of Conditional Survival in Gastric Cancer Reveal a Reduction of Racial Disparities with Long-Term Follow-Up

Abstract: Our investigation shows that racial disparities in gastric cancer outcomes are pronounced at the time of curative surgery but diminish after years of survival, thus suggesting race has less influence over outcomes the longer patients survive. The reasons for reduction of racial disparities remain unclear and warrant future study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 20 publications
1
12
0
2
Order By: Relevance
“…one is limited in using previous literature values to calculate conditional survival because it requires 5 additional years of follow-up and survival results. the trends are also not surprising when compared with those of other cancer sites, such as colon, 7 rectum, 8 colorectal, 15 stomach, 11,16,17 liver, 18 head and neck, 19 ovary, 10 thymus, 20 thyroid, 21 lial carcinoma. 26,27 all of these solid tumors show more dramatic improvements in prognosis in more advanced stages of cancer.…”
Section: Discussionmentioning
confidence: 87%
“…one is limited in using previous literature values to calculate conditional survival because it requires 5 additional years of follow-up and survival results. the trends are also not surprising when compared with those of other cancer sites, such as colon, 7 rectum, 8 colorectal, 15 stomach, 11,16,17 liver, 18 head and neck, 19 ovary, 10 thymus, 20 thyroid, 21 lial carcinoma. 26,27 all of these solid tumors show more dramatic improvements in prognosis in more advanced stages of cancer.…”
Section: Discussionmentioning
confidence: 87%
“…However, the unique findings of this study showed that while both short-and long-term outcomes were superior at high volume centers, these benefits may not be equally appreciated by all patient populations. Health care treatment disparities have been previously identified for patients with either esophageal (16,30) Table 3 Baseline demographics, tumor characteristics, and short-term outcomes for patients with gastric cancer (adenocarcinoma) treated with total gastrectomy as stratified by hospital case volume-low: 1-99 cases per decade, middle: 100-200 cases per decade, and high: >200 cases per decade or gastric cancer (17,25,31). This study provided an indepth analysis demonstrating that health care disparities vary by institution based on case volume for the selected oncologic procedures, with fewer disparate factors present at high volume centers.…”
Section: Discussionmentioning
confidence: 99%
“…The CS estimate, a novel prognostic index, provides new information relevant to the dynamic prognostic changes that occur for patients with gastric cancer. Several studies have shown that CS estimates are highly significant to the evaluation of the prognostic prospects of patients with various malignant diseases [ 4 , 6 16 , 20 ]. Furthermore, it is generally accepted that patients with poor prognostic features at the time of initial diagnosis show, compared with those without these features, greater increases in CS over time.…”
Section: Discussionmentioning
confidence: 99%